PEMANFAATAN POTENSI SUMBER DAYA LOKAL DESA TRIDHARMA SEBAGAI PENGEMBANGAN DESA KETAHANAN PANGAN - Agus Bahar (Jambura Journal of Husbandry and Agriculture Community Serve (JJHCS), 2022)
In Tridharma Village, Pulubala District, Gorontalo District, that corn is the dominant local resource potential in this village. In addition, coconut and fro are also one of their local resources. Previously, horticultural crops such as chilies and tomatoes were a potential resource for this village, but this has stopped because the prices of horticultural crops have always decreased. The abundant potential of local resources in the field of food security is not accompanied by good utilization by the village community. The village community prefers to sell their crops in the form of goods that have not been processed (raw goods) so that the profits obtained by Tridharma village farmers are relatively small. Regarding stunting in Tridharma Village, Pulubala District, Gorontalo Regency, there are 15 children who are indicated to be stunted. As well as facilities that support the potential of young people in Tridharma Village, sports facilities are not available. The objectives of this activity are: to improve the performance of UNG Lecturers through community empowerment; implementing research results of service lecturers through dedication in the form of village community empowerment; development and application of technology that is useful directly in society; establish cooperation with government agencies and stakeholders to improve the quality of community service at Gorontalo State University. The field of food security, namely: (1) Making beds and fertilizing (2) Providing socialization and management of corn and kolang kaling products which are the potential of Tridharma Village. The Stunting Field, namely: (1) Going to the field to collect data on pregnant women and children who are indicated to be stunted (2) Providing counseling on 1000 HPKs at the toddler posyandu (3) Providing food in the form of fruit as a form of prevention through the toddler posyandu. The field of sports facilities, namely: (1) Providing a takraw field as a means of supporting the hobbies of young people in Tridharma village (2) Creating a takraw competition as an event to enliven the village and look for potential seeds in Pulubala sub-district.We hope that there will be follow-up in the future by the village and this realization can be continued by the next Thematic KKN Students so that the various activities and programs that have been carried out are not interrupted in the Thematic KKN 2022. We have great hopes that in the future a brilliant and sustainable program can be created. It is hoped that the community and the Village Government will continue to work together in building and advancing Tridharma Village, Pulubala District, Gorontalo Regency.